Determinants of Mobility in the Middle-Income Classes for Turkiye - Banu Beyaz Sipahi (Journal of Economy Culture and Society)
This paper contributes to the literature by examining mobility in the middle-income classes for Turkiye. In this context, this study’s aim is to present a profile of the middle-income class in Turkiye and identify the effects of socio-economic and demographic factors on the transition from a middle-income class to a lower income group and upper income group using a probit model. The middle class was determined using the relative income measure. The data used in the analyses are based on the Income and Living Conditions Surveys (ILCS) by the Turkish Statistical Institute (Turk Stat) over the period 2015-2018. The results of the analysis indicate that the age, gender, education level, marital status, employment status housing ownership type of the households, and income type affect the transition of middle-income classes into lower or upper income classes in different ways. Accordingly, in cases where the head of the household is male, household members are young, household members have a high education level, and where there are a small number of members in the household, all negatively affect the probability of transitioning from a middle-income class to a low-income class. In contrast, it positively affects the transition to a high income class.